The Generalized Projective Riccati Equations Method for Solving Nonlinear Evolution Equations in Mathematical Physics - E. M. E. Zayed; K. A. E. Alurrfi (Abstract and Applied Analysis)
We apply the generalized projective Riccati equations method to find the exact traveling wave solutions of some nonlinear evolution equations with any-order nonlinear terms, namely, the nonlinear Pochhammer-Chree equation, the nonlinear Burgers equation and the generalized, nonlinear Zakharov-Kuznetsov equation. This method presents wider applicability for handling many other nonlinear evolution equations in mathematical physics.